Self-Efficacy As Mediator Of The Influence Of Entrepreneurship Education And Entrepreneurial Attitudes On The Entrepreneurial Interest Of Students At Tirta Sari Surya Vocational School - Lusyiana, Alsya; Faslah, Roni; Adha, Maulana Amirul (Business and Investment Review, 2025)
This study aims to explore the impact of entrepreneurship education and entrepreneurial attitudes on students' interest in entrepreneurship, considering self-efficacy as a mediating variable. The subjects in this study were students from SMK Tirta Sari Surya, with a total of 215 respondents. The method used is a quantitative approach, and data analysis was conducted using Partial Least Square (PLS) through the SmartPLS version 4 application. The findings of the study indicate that entrepreneurship education has a direct impact on self-efficacy and interest in entrepreneurship. Additionally, entrepreneurial attitudes also show a direct influence on self-efficacy and interest in entrepreneurship. Self-efficacy was found to have a significant direct influence on interest in entrepreneurship. The mediation analysis results indicate that self-efficacy can act as a mediator in the relationship between entrepreneurship education and entrepreneurial attitudes with interest in entrepreneurship. This finding underscores that students' interest in entrepreneurship is not only influenced by the learning process at school and individual attitudes but also heavily depends on how much they believe in their own abilitie